Science & Technology Studies Elsewhere A Postcolonial Programme - Hofmänner, Alexandra (Schwabe Verlag, 2020)
In April 2017, scientists took to the streets in a historically unprecedented Global March for Science. The event was seen as symbolic of a crisis in the relationship of science and society. This book considers the Global March for Science from a postcolonial perspective to inquire into the toolkit that the academic field of Science & Technology Studies (STS) has to offer. It argues that new concepts and analytical approaches are necessary to investigate current global dynamics in science, technology and society, so as to deliver insights that the recent expansion of STS scholars beyond Western Europe and North America alone is unlikely to provide. The book presents a Programme in Science Studies Elsewhere (SSE) to demonstrate the urgent need to carry postcolonial issues right into the centre of STS's intellectual programme.